Couples' Experience of Enactment-Based Couple-Centered Intervention vs. Therapist-Centered Intervention—An Exploratory Qualitative Examination. Issue 1 (2nd January 2023) - Butler, Mark H.; Ballard, James W.; Crawford, Misha D.; Seedall, Ryan B.
Abstract: Enactments represent a clinical process and structure common to marital therapy, consisting of episodes of direct couple engagement carefully promoted, monitored, and coached by the therapist. Couple-enactment-centered therapy is supported by a relational systems theory rationale for interaction-focused intervention. We specifically explored couples' experience of relationship enactments and their potential to promote positive relationship interaction and outcomes. In an experimental design, participant couples received three couple-enactment-centered sessions (intervention through couple interaction) followed by three therapist-centered sessions (intervention through therapist interaction), with sequencing randomly alternated (CECx3–TCx3 or TCx3–CECx3). In this study, through qualitative interviews we sought the voices, perceptions, and experiences of couples regarding these modalities and their potentially unique utility. Qualitative data from 12 participants was analyzed using a group hermeneutic approach. Findings included that (a) therapeutic alliance, achieved in a more salient way through TC, was important to positive clinical and couple outcomes, (b) the sequencing of approaches was significant, and (c) modality (CEC or TC) influenced participant experience of relational change. Our discussion hypothesizes a general profile of participants' experiences of these two approaches in therapy, contributing to an emerging framework potentially informing best couple therapy practice utilizing both TC and CEC modalities in sequence.